Net-phytoplankton communities and influencing factors in the Antarctic Peninsula region in the late austral summer 2019/2020 - Liu, Lu; Zhang, Jichang; Zhao, Yunxia; Luan, Qingshan; Zhao, Xianyong; Wang, Xinliang (Frontiers in Marine Science, 2023)
The waters near the Antarctic Peninsula are characterized with unique oceanographic conditions and rich krill resources. In present study, the net- phytoplankton community structure and major biotic and abiotic factors over that community were investigated. Samples were collected at 40 stations near the South Shetland Islands (SSI) during the austral summer of 2019/2020. Eighty-one taxa were identified by light microscope, and diatoms were the most abundant group. The most abundant species were Chaetoceros atlanticus, C. criophilus, C. dichaeta, Fragilariopsis kerguelensis and Pseudo−nitzschia lineola. The abundance and Shannon-Weaver index of net-phytoplankton ranged from 100 to 2.64×107 cells/m3 and 0.0747 to 4.0176 respectively, with significantly low values detected in the Bransfield Strait (BS) and high values in the west of the SSI, highlighted by the Cluster Analysis. The dissimilarity was mainly caused by the differences in abundance of diatoms (including Thalassiothrix antarctica and the species in genus Rhizosolenia, Chaetoceros, Fragilariophsis). These diatoms and Dictyocha speculum were found in higher abundance in the west of the SSI, while Corethron pennatum and cryptophytes were found in higher abundance in the BS. Combined with acoustic density of krill and environmental data (Sea Surface Temperature and Sea Ice Concentration), an ordination approach was applied, and then, there was noteworthy that SST positively affected the phytoplankton community while other factors had insignificant effect. We suggest that acoustic- derived krill density would be associated with the spatial distribution of pennate diatoms. This enhances the knowledge about the selective feeding for krill and ecological implications for the Antarctic systems.